Legality and Legitimacy - Dyzenhaus, David (Clarendon Press, 1997)
This study looks at one of the oldest questions in legal philosophy--the relationship between law and legitimacy. Dyzenhaus analyzes the legal theories of three eminent public lawyers of the Weimar era whose theories addressed the problems of legal and political order in a crisis-ridden modern society and demonstrates their relevance to contemporary debates